TINJAUAN HUKUM PIDANA ISLAM TERHADAP SANKSI TINDAK PIDANA PEMERKOSAAN PADA ANAK DI BAWAH UMUR (Studi Putusan Nomor 3/Pid.Sus-Anak/2019/PN Msh) - Sarika Sarika; Erniwati Erniwati (Universitas Islam Negeri Raden Fatah Palembang, 2023)
The crime of rape is often experienced by children who are relatively young (underage). In children, the innocent nature of a child who is unable to predict behavioral tendencies will make it easier for rape crimes to occur. Children who are still very economically and socially dependent on adults are often used as an outlet for their desires. The focus of the study in this thesis is: 1. What is the basis for the judge's considerations in deciding sanctions for the crime of rape of minors (Decision Study Number 3/Pid.Sus-Anak/2019/PN Msh). 2. What is the review of Islamic criminal law regarding sanctions for the crime of rape of minors (Decision Study Number 3/Pid.Sus-Anak/2019/PN Msh). This research uses a normative juridical approach. The data source for this research is primary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique was carried out by means of library research. The results of this research conclude that the Judge's Basic Considerations Number 3/Pid.Sus-Anak/2019/Pn/Msh in cases of rape of minors took into account juridical and sociological considerations by sentencing the defendant to imprisonment for 3 (three) years and 6 (six) months at the Special Child Development Institute (LPKA), and Job Training for 1 (one) month, and a review of Islamic criminal law regarding decision Number 3/Pid.sus-Anak/2019/Pn/Msh is hudud law, where the punishment is included in the Jarimah of adultery, the punishment is being whipped 100 times and exiled for a year. Keywords: Child Rape, Criminal Sanctions, Adultery.